PENGARUH VIDEO EDUKASI TERHADAP PENGETAHUAN SAFETY RIDING PEKERJA FINISHING PT X TANGERANG - Naranti Putri, Alliya Azmi; Widjanarti, Maria Paskanita; Cahyanto, Erindra Budi (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
The number of traffic accidents that have been experienced by the workers of PT X Tangerang between 2020 and 2021 has increased and dominated by the finishing workers of PT X Tangerang. 80-85% accidents happened because of unsafe action by an individual due to lack of knowledge. This research aims to find out the effect of educational video for safety riding knowledge of finishing workers in PT X Tangerang. This research employed a quacy-experimental with a pretest-posttest control group with a respondent of 60 workers, 30 workers in each experimental and control group selected using simple random sampling technique. The result of the analysis in the experimental group using the Marginal Homogeneity test showed that there was a significant effect (p = 0,016) of the safety riding knowledge of the finishing workers before and after the intervention using the safety riding educational video. Meanwhile in the control group, there was no significant difference (p = 0,317) of safety riding knowledge based on the pre-test and post-test results. The Chi-Square test result showed the p value of 0,042 meaning that there was a significant effect of safety riding knowledge between the experimental which was given the intervention and the control group which was not. The conclusion of this study is Educational video has a significant effect towards safety riding knowledge of finishing workers in PT X Tangerang.